Living conditions among recyclable waste pickers:: integrative literature review (Sustainability in Debate, 2018)
This present paper consists in an integrative review whose aim is to analyze the scientific studies that shed a light on the state of art of the living conditions of recyclable waste pickers. Information on the living, health and work conditions presented in secondary papers related to publications of the last ten years (2004-2014) was retrieved, considering the scientific productions registered in the databases of the Virtual Health Library and Proquest. Finally, eight articles were found. It was evidenced that the collectors are inserted in a context of social vulnerability related to their position in society and that conditions such as profile, educationand socioeconomic factors interfere in their quality of life. It is concluded that it is necessary to invest in in-depth research to construct interventions of health promotion and prevention of health problems directed specifically to this strategic public, understanding that the scientific studies can drawmore attention of municipal, state and federal managers.